Nontarget Metabolites of Rhizomes of Edible Sacred Lotus Provide New Insights into Rhizome Browning - Chenyang Hao; Yuetong Yu; Xueting Zhang; Gangqiang Dong; Yan Liu; Sha Chen (Journal of Food Quality)
The “edible rhizome” variant of Nelumbo nucifera with various cultivars has a long history of use as a food in East Asia. In this study, 48 target metabolites were untargeted and identified in 212 rhizome cultivars (tropical and temperate types) using ultraperformance liquid chromatography-electrospray ionization quadrupole time-of-flight high-resolution mass spectrometry; among these, 32 compounds were newly reported in the rhizome. Combined with the browning phenotype of 212 lotus rhizomes, (epi) catechin, norarmepavine, and N-feruloyl-3-methoxytyramine were used as predominant chemical markers to separate different degrees of lotus rhizome browning. p-Coumaroyltyramine and N-trans-feruloyltyramine were selected as predominant chemical markers to investigate the differential expression between tropical and temperate lotus using principal component analysis and orthogonal partial least squares discriminant analysis. Shared and unique structure plots were used to compare the outcomes of the ecotype and browning OPLS model, showing that variation in tropical lotus rhizome browning is not obvious; this will be of great importance for genetic improvement by providing a hereditary basis.